MAGNETIC PHASE TRANSITIONS IN (Er_xNd_1-x)_2Fe_14B H_3,4 INTERMETALLIC HYDRIDES - Aghababyan, E. V.; Harutyunyan, N. P.; Nikitin, S. A.; Pankratov, N. Yu. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2007)
The magnetic susceptibility and the magnetization of magnetic ordering compounds (ErxNd1-x)2Fe14B and their hydrides were investigated. It is found, that in this compounds a variety of spin-reorientation transitions (SRT) depending on containing in alloys concentration Er were observed. The temperatures of SRT were determined. The hydrogenation of above indicated compounds do not change the nature magnetic phase transitions, but it influences over temperature of SRT. The transformat ion of spin-reorientation transitions and magneto crystallographic anisotropy is explained by contrary sign coefficients of Stivens for Er and Nd differently interacted with crystallographic field 3d-under grating, distorted by insertion of hydrogen atoms.